Microelectronic circuits analysis and design - Rashid, Muhammad H. (Cengage Learning, 2017)
This book introduces general characteristics of circuits (ICs) to prepare students for circuit design and analysis techniques. More than half of the problems and examples concentrate on design and use software tools extensively.